GASTROPROTECTIVE ACTIVITY OF COMBINATION ARROWROOT STARCH (MARANTA ARUNDINACEA) AND ETHANOL EXTRACT OF PROPOLIS (TRIGONA SP) ON RATS ULCER MODEL - Ayuna Faikar, Rifasya
Peptic ulcer is a problem in the gastrointestinal system, characterized by damage to the mucosal layer due to excessive secretion of pepsin, gastric acid, or a decrease in protective factors for the stomach. Garut tuber starch and propolis are known to have potential as gastroprotective agents individually. This study aims to compare the gastroprotective activity of the combination of Garut tuber starch and ethanol extract of propolis with their respective single doses. The main parameters used are the gastric ulcer index and the percentage inhibition of gastric ulcers. Other supporting parameters include pH measurement and gastric fluid weight. The testing was conducted on six groups, namely the normal group (0.5% CMC-Na), negative control group (0.5% CMC-Na), positive control group (200 mg/kg BW sucralfate), starch group (250 mg/kg BW), ethanol extract of propolis group (50 mg/kg BW), and combination group with half of the single dose (125 mg/kg BW starch and 25 mg/kg BW ethanol extract of propolis). The observation was carried out for 14 days, with the negative, positive, starch, propolis, and combination groups induced with 96% ethanol at a dose of 1 ml/200g BW except for the normal group, followed by an 18-hour fasting period on the 15th day. After one hour of induction, all rats were sacrificed, and their stomachs were collected for observation. The results of the study showed that the combination group had a lower ulcer index of 2.20 and the highest inhibition ability of 45% compared to the other groups. The combination group did not differ significantly from the negative group in terms of pH reduction. However, it showed significant differences from the negative group in terms of gastric fluid weight. Histological results indicated that the combination group had mucosal layer conditions similar to the normal group, and there was evidence of epithelial layer improvement. Based on these findings, it can be concluded that the gastroprotective effect of the combination of Garut tuber starch and ethanol extract of propolis at a ½-½ dose is comparable to the individual effects of Garut tuber starch and ethanol extract of propolis. The nature of this combination is additive.